Modulatory effects of main Mango (Mangifera indica L. cv. “Ataulfo”) phenolics on the growth of selected probiotic and pathogenic bacteria - Pacheco-Ordaz, R. (2018)
Fruit extracts from different tissues (pulp, seed and peel) have shown antimicrobial and prebiotic activities related to their phenolic profile, although structure-specific evaluations have not been reported yet. The effect of five phenolic compounds (catechin and gallic, vanillic, ferulic and protocatechuic acids) identified in different fruits, particularly in mango, was evaluated on the growth of two probiotic (Lactobacillus rhamnosus GG ATCC 53103 and Lactobacillus acidophilus NRRLB 4495) and two pathogenic (Escherichia coli 0157:H7 ATCC 43890 and Salmonella enterica serovar Typhimurium ATCC 14028) bacteria. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of phenolic acids ranged from 15-20 mmol and 20-30 mmol against E. coli and S. Typhimurium , respectively. For catechin, the MIC and MBC were 35 mmol l 1 and 35 mmol l against E. coli and S. Typhimurium , respectively. The presence of catechin and gallic, protocatechuic and vanillic acids in MRS broth without dextrose allowed the growth of lactobacilli. Catechin combined with protocatechuic or vanillic acid mildly allowed the growth of both probiotics. In conclusion, phenolic compounds can selectively inhibit the growth of pathogenic bacteria without affecting the viability of probiotics